Non-fiction on the boundary of XX–XXI centuries: theoretical aspect - Novik, Hanna Y. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to theoretical understanding of the phenomenon of non-fiction and its role in the contemporary literary process in Belarus. We consider synonymous terms, which are used for the category of documentary – «ego-doсument», «literature of fact», «uninvented literature», «literature with dominant documentary beginning», and others, including exclusive «self-life-description», «chronicle of the life and work», «literature of existence», etc. It showed the genesis of non-fiction, which dates back to the literary salons of XIX century, Russian literary association «LEF» 1922–1928 years and the American «new journalism» of 1960s. Based on the reference to the works of Belarusian writers of the turn of XX–XXI centuries we reveal the most important genre features of non-fiction literature. Summed findings allow us to consider non-fiction at the same time as the writing method; as a subsidiary body of texts created without the participation of fiction; as a collection of literary works written by said method. Also carried concretization of the concept of non-fiction, which interpreted abstractly by many literary critics.
Keywords: documental literature; non-fiction; autobiographical prose; fiction; fact; the document